A literature review on effects of regular exercise on cognitive function in older adults - Lompart, Albert; Wabiszczewicz, Michał; Kosarewicz, Albert; Woźniak, Łukasz; Krysiak, Patrycja (Quality in Sport, 2025)
Purpose This review investigates how exercise affects cognitive function in older adults, focusing on recent evidence and mechanisms. The aim was to assess the impact of various exercise types on cognition in healthy and cognitively impaired older people. Methods A systematic review covered randomised controlled trials, systematic reviews, and meta-analyses from 2018–2025 involving participants aged 60+ and examining exercise effects on cognition. Results Regular physical activity benefits multiple cognitive domains. Aerobic training improves global cognition (effect sizes 0.28–0.76). Resistance training shows stronger effects on executive function (SMD up to 0.80). Combined programmes enhance attention, executive skills, and overall cognition. Mind-body exercises, e.g., Tai Chi, also improve memory and executive functions. These effects are related to higher brain-derived neurotrophic factor levels, neuroplasticity, and brain structure changes. Conclusion Exercise is an effective non-pharmacological method to support cognitive health in older age. Different forms provide distinct advantages: aerobic training benefits global cognition, resistance supports executive function, and multicomponent programmes offer broad cognitive improvements. Evidence supports including structured exercise in clinical guidelines and public health measures to maintain cognition in ageing populations.